OMERACT agreement and reliability study of ultrasonographic elementary lesions in osteoarthritis of the foot - Carlo Alberto Scirè (BMJ Publishing Group, 2019)
ObjectiveTo evaluate the level of agreement on ultrasonographic (US) lesions among highly experienced sonographers as well as the intraobserver and interobserver reliability of inflammatory and structural US lesions in patients with osteoarthritis (OA) of the foot.MethodsAfter a systematic literature review, a Delphi survey was performed to test definitions of US lesions in OA of the foot, including inflammatory lesions (ie, synovial hypertrophy [SH], joint effusion [JE], power Doppler signal [PD]), and structural abnormalities (ie, cartilage damage [CD] and osteophytes). Subsequently, the reliability of US in assessing the aforementioned lesions was tested on static images as well as during a live exercise. Reliability was assessed by kappa analyses and prevalence-adjusted bias-adjusted kappa (PABAK) on a dichotomous and an ordinal scale.ResultsIntraobserver and interobserver reliability for SH and JE evaluated by binary scoring was good for both components, while the intraobserver reliability for semiquantitative scoring of SH ranged from moderate in the web-based exercise (PABAK 0.49) to good (PABAK 0.8) in the live exercise. Reliability for CD and PD assessments were respectively good and excellent in all exercises (ranged from PABAK 0.61 to 0.79 for CD and 0.88 to 0.95 for PD). The interobserver reliability for the semiquantitative scoring of osteophytes was fair in the live exercise (PABAK 0.36) and moderate in the static exercise (PABAK 0.60).ConclusionsConsensual US definitions were found to be reliable for assessing inflammatory lesions in OA of the foot, while the use of US to assess structural damage requires further studies.